Baby dinosaurs on the ark?: the Bible and modern science and the trouble of making it all fit - Ray, Janet Kellogg (Wm. B. Eerdmans Publishing Co., 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by Deborah Haarsma -- Acknowledgments -- 1. The Biology Professor Who Doesn't Believe in Science -- 2. Making Science Fit Genesis -- 3. What Is Science? The Nature of Science and EVO 101 -- 4. Where Are You Camping? A Look at Beliefs -- 5. There Might Be a Time Machine in Your House -- 6. It's Raining, It's Pouring, the Canyon Is Forming: Noah's Flood Explains It All -- 7. The Flood and the Fossil Record -- 8. Written in Stone -- 9. In Search of the Missing Missing Link -- 10. It's All or Nothing: Intelligent Design -- 11. You Can't Make a Monkey Out of Me: The Touchy Topic of Human Evolution -- 12. Leaving Creationism (Without Leaving God) -- Notes.